1 bit encoding–decoding-based event-triggered fixed-time adaptive control for unmanned surface vehicle with guaranteed tracking performance. (June 2023) - Song, Xiaona; Wu, Chenglin; Stojanovic, Vladimir; Song, Shuai
Abstract: This paper investigates the fixed-time prescribed performance trajectory tracking control for the unmanned surface vehicle with unknown dynamics and disturbances. At first, an improved prescribed performance function was introduced to transformation of coordinate for achieving a user-defined performance including the transient and steady-state performance of the USV. Then, an adaptive fixed-time trajectory tracking controller is designed by integrating the fixed-time stability and the event-triggered control (ETC) mechanism. Stability results prove that the proposed controller not only guaranteed that all the signals in the closed-loop system are the semi-global uniform ultimate bounded (SGUUB), but also ensured the tracking errors can converge to a preassigned area in a fixed-time. Moreover, by proposing a co-design of the ETC and 1-bit signal encoding–decoding mechanisms between controller and actuator, the trade-off between tracking performance and communication cost is achieved. Finally, the effectiveness of the developed control approach is verified through simulation results.